Methodology in religious studies : the interface with women's studies - Sharma, Arvind (McGill studies in the history of religions., 2002)
"Methodology in Religious Studies assesses the impact of women's studies on the various methods employed in studying religion. Since its inception in the 1860s, the study of religion as an academic discipline has evolved over time, ranging from the classically historical to the boldly hermeneutical. The women's studies movement has, since the 1980s, become part and parcel of the intellectual landscape of our times, and the study of religion has become increasingly influenced by it. What are the implications of this new development for the methodology of religious studies? Leading practitioners of psychological, theological, sociological, anthropological, phenomenological, historical, and hermeneutic approaches examine the mutually enriching interface between religious studies and women's studies, as they explore the broader issue of the interaction between method and the nature of the subject itself."--Jacket